An Intermittent Karst River: The Case of the Čikola River (Dinaric Karst, Croatia) - Ognjen Bonacci (Water, 2019)
Intermittent and ephemeral streams (IRES) are responsible for transporting about half of the water on Earth’s surface. Their hydrological behavior is different in various landscapes. IRES are found more often in karst terrains than in any other regions, as a consequence of strong and direct interaction between groundwater and surface water. This paper presents a hydrogeological and hydrological analysis of the intermittent Čikola River and Spring catchment, which is located in deeply karstified and developed parts of the Dinaric karst in Croatia. Hydrological calculations determined that the catchment area covers approximately 300 km2 and very probably changes in accordance with rapid variations in groundwater level. The karst spring of the Čikola River is a cave, extracted for a public water supply with four drilled extraction wells. The results of the interrelated hydrological and hydrogeological analysis show interesting phenomena from an intermittent karst spring (cave) and its catchment, flowing downstream through a karst polje with several smaller confluences, then entering a karst canyon (where the river sinks during certain periods), and ending in an estuary before contributing to the larger Krka River. The research presented was based on water balance calculations, climatic and hydrological time series analyses, spring pumping tests, and thorough hydrogeological interpretation.